Uji Organoleptik Kopi Biji Salak dengan Varian Waktu Penyangraian - Eka Lokaria; Ivoni Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to see the effect of roasting time on organoleptic tests of banjarnegara zalacca coffee beans (Salacca zalacca var zalacca). The effect of the treatment was determined using the Completely Randomized Design (CRD) method which consisted of six treatments and three replications. The treatments are P0 namely control, P1 with a roasting time of 40 minutes, P2 with a roasting time of 50 minutes, P3 with a roasting time of 60 minutes, P4 with a roasting time of 70 minutes and P5 with a roasting time of 80 minutes. Based on the one way anova test with a significant level of 5%, it showed significant results, namely F-count (6.42)> F-table (3.68), followed by LSD test which obtained significantly different results in the P3 treatment (60 minutes) with BNT number 2.67. The best roasting time for zalacca coffee in P3 treatment with 60 minutes roasting time which has dark brown color criteria, very fragrant aroma, smooth texture, bitter taste, and very acceptability. The results showed that the higher the quality of zalacca coffee the higher the people's acceptance of zalacca coffee. Keywords: salak banjarnegara seeds, roasting, organoleptic